CORAK PEMAHAMAN KARYAWAN KEMENTERIAN AGAMA KABUPATEN REJANG LEBONG TERHADAP KONSEP TAKDIR DAN KOHERENSINYA DENGAN ETOS KERJA (STUDI TEOLOGIS PEMAHAMAN TENTANG TAKDIR DAN ETOS KERJA) - Ombi Romli (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: The purpose of this study is to know about  the style of understanding the concept of destiny employees of the Ministry of Religious Rejang Lebong. The work ethic of employees Ministry of Religious Rejang Lebong and how coherence between the understanding of destiny with the work ethic. Research conducted qualitative,  with a phenomenological approach. Who became an informant as a data source is partially employee Rejang Lebong Religious Affairs totaling 25 people, consisting  of the organization’s  leaders, the heads of sections., Organizer and supervisor of the Islamic religion and the staff all of whom are Muslims. Then the research data were analyzed using analytical techniques deskriftik. In this study, the authors wanted to know and to describe, the following matters: First, the style of understanding the concept of destiny employees of the Ministry of Religious Rejang Lebong, author klsifikasikan  to tigaa jabariah  pattern that is moderate, that gives meaning to the concept of destiny  will be the synergy between the absolute freedom of God with the power of human endeavor. In addition there are patterned qodariah, who interpret memaberikan broadest freedom to power  and the power  of man, and the last, patterned extreme jabariah, who interpret destiny is the prerogative of God, men  did not take part in it, like a puppet-driven human puppeteer. Second, the  Ministry of Religious Affairs Employees Work  Ethic Rejang  Lebong.  The result shows that in general, his work ethic were high. With the following indicators: a). Employee attitudes toward work:1.Fleksibilitas while  working  2. Adjustment of work b). Feelings  of an employee: 1. Control 2. senag  bekerja. c job). The willingness of the employees to do the job: 1. Compliance work, 2. Willingness to complete the work, d). employees currently work: 1. The seriousness of the work The third of the coherence between the understanding of the concept of destiny  with the work ethic.  From the data  I have found  the results,  that there  is a significant relationship between the understanding of religious ministry employees destiny Rejang Lebong with his work ethic. Broadly speaking, that employees who patterned jabariah  moderate ideology and Qodariyah  work ethic tends  to be high, employees were shades of understanding destiny jabariah extreme work ethic tends to be low.